The effect of e-service quality on consumers’ satisfaction and loyalty in online shopping - Lusianus Kusdibyo (International Conference on Industrial Revolution for Polytechnic Education, 2021)
The purpose of this study is to measure the influence of electronic service quality on consumers’ satisfaction and loyalty in online shopping setting. The questionnaires were distributed online. Of the 305 returned questionnaires, 282 were eligible for further data analysis. SEM-PLS was used to test the hypothetical analysis. The results reveal that e-service quality has a positive and significant influence on satisfaction. Also, consumers’ satisfaction influences positively and significantly on loyalty. The indirect effect of e-service quality on loyalty is higher compared to its direct effect. This means that satisfaction is important variable in shaping customers’ loyalty. In addition, the dimensionality of e-service quality needs to be further tested as the result did not conform to the previous study. Academically this study provides better understanding on the relationship between e-service quality, satisfaction and loyalty in an online shopping context. Practically this study contributes to the online shop businesses by providing evidence on the importance of the e-services quality dimensions and the need to satisfy customers to get their loyalty. Online shop businesses need to determine and focus on relevant e-service quality dimensions in building their online shop competitiveness.